A Case of Covid-19 Respiratory Illness with Subsequent Seizure and Hemiparesis: - Hamidi, Ava; Sabayan, Behnam; Sorond, Frazaneh; Nemeth, Alexander J; Borhani-haghighi, Afshin (Galen Medical Journal, 2020)
Background: Neurological manifestations and complications are common in viral infections, and they are significant sources for clinical deterioration and poor clinical outcomes. Case report: The current report presents a 38year-old man with Covid-19 respiratory illness who subsequently developed neurological complications and clinical worsening leading to death. This patient sought medical attention after five days of progressive cough, fever, and dyspnea. On arrival in the emergency room, he was found to have hypoxic respiratory failure resulting in intubation and intensive care unit (ICU) admission. Chest CT scan was characteristic for Covid-19 infection, and PCR test on tracheal samples confirmed the diagnosis. On day nine of admission, he developed generalized tonic colonic seizure associated with deterioration of mental status and hemiparesis. Repeated brain CT scans showed subcortical hypoattenuation with associated sulcal effacement in the left occipital and posterior parietal lobes concerning for ischemic changes. The patient passed away on day 17 despite supportive measures. Conclusion: This observation and recent evidence on Covid-19 CNS involvement highlight the need for further studies on early recognition of neurological complications in Covid-19 patients. [GMJ.2020;9:e1915]